Complex aesthetic rehabilitation with lithium disilicate veneers - Wijaya, Wina M.; Murti Indrastuti; Intan Ruspita; Titik Ismiyati (Indonesian Journal of Prosthodontic, 2025)
Currently, demand on society for dental aesthetics has become increase especially dental veneer. Minimal invasive technique is the most advantageous technique in dental veneer due to pulp tissue remained safe and aesthetic aspect fulfilled. In this case is to give detail of aesthetic procedure to correct irregularities anatomical of the teeth using lithium disilicate veneers. A 20-year-old female patient came with a complaint of multiple diastema on anterior upper teeth. Based on objective examination 12 and 22 having peg-shaped and 53 maintain prolonged retention, agenesis and still sufficient. Multiple diastema between 53, 12, 11, 21, 22 and 23. Crown lengthening was performed on 53 to improve inciso-gingival ratio and tooth preparation for this case were using minimal invasive. Six units of lithium disilicate indirect veneer were placed using resin cement. Indirect veneers are placed with overjet and overbite are 3 mm, there is no changing contact maxillary and mandibular prior and following placement indirect veneers. Minimal invasive preparation involves in making the space needed for the restorative material of choice, outlining requirements for aesthetic needs, and outlining requirements that will make fabrication easier and created satisfactory result. After 2 months follow-up, veneers still retained well and stable, the veneers colour resembles natural teeth, tissue adaptation was also performed good and the patient is satisfied with the treatment results. Lithium disilicate veneers can be used as a treatment option for anterior teeth with deformities and primary tooth which still sufficient was performed. Keywords : indirect veneer; peg-shaped; primary tooth; lithium disilicate; cosmetic dentistry